REVENGE IN EMILY BRONTË’S NOVEL WUTHERING HEIGHTS - Safitri, Lia; Asnani, Asnani (JOURNAL OF LANGUAGE, 2024)
The research seeks to uncover the causal factors and detrimental effects of revenge as depicted in Emily Bronte’s novel, Wuthering Heights. Given its focus on societal phenomena, the chosen methodology is the descriptive qualitative approach, aimed at elucidating these social dynamics. The analysis draws upon theories of revenge proposed by Barcaccia et al. and Schwartz, which respectively delve into the underlying elements of vengeance. Revenge arises from a potent desire to seek retribution for perceived injustices, often manifesting as the infliction of harm or suffering upon the perceived wrongdoer. However, rather than achieving justice, revenge often perpetuates a cycle of retaliation, as individual interpretations of moral equilibrium seldom align. Wuthering Heights serves as the primary source of data, with textual excerpts informing the analysis. The findings reveal three primary instigators of revenge: betrayal, injustice, and insult, with resultant negative impacts including depression and anxiety.